Write and publish your pedagogical experience in PM. (Journal of Parents and Teachers, 2025)
The article emphasizes the importance of transmitting and contributing to teacher training through the media. Within journalistic genres, there are several items or subdivisions: informative, opinion, and advertising. Additionally, the text should be understandable, engaging, clear, and concise. And, of course, it should include titles, subtitles, and headings.
Keywords: text; information; transmit; comunication medium